Longitudinal transcriptome analysis of cattle infected with Theileria parva. Issue 13 (December 2022) - Chepkwony, M.; Wragg, D.; Latré de Laté, P.; Paxton, E.; Cook, E.; Ndambuki, G.; Kitala, P.; Gathura, P.; Toye, P.; Prendergast, J.
Graphical abstract: Highlights: The host transcriptional response across 29 cattle exposed to buffalo-derived Theileria parva challenge was characterised. Genes (64) differentially expressed between cattle that survived and succumbed were identified. We identified 1958 genes whose response to infection depended on the genotypes of nearby variants. Abstract: The apicomplexan cattle parasite Theileria parva is a major barrier to improving the livelihoods of smallholder farmers in Africa, killing over one million cattle on the continent each year. Although exotic breeds not native to Africa are highly susceptible to the disease, previous studies have illustrated that such breeds often show innate tolerance to infection by the parasite. The mechanisms underlying this tolerance remain largely unclear. To better understand the host response to T. parva infection we characterised the transcriptional response over 15 days in tolerant and susceptible cattle ( n = 29) naturally exposed to the parasite. We identify key genes and pathways activated in response to infection as well as, importantly, several genes differentially expressed between the animals that ultimately survived or succumbed to infection. These include genes linked to key cell proliferation and infection pathways. Furthermore, we identify response expression quantitative trait loci containing genetic variants whose impact on the expression level of nearby genes changes in response to the infection. These therefore provide an indication of the genetic basis of differential host responses. Together these results provide a comprehensive analysis of the host transcriptional response to this under-studied pathogen, providing clues as to the mechanisms underlying natural tolerance to the disease.